Empirical review on determinants of potato and onion production technology packages adoption in Ethiopia - Oliyad Sori Zenbaba (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Vegetable production technology packages adoption is essential for intensifying its productivity thereby improve the income of smallholder farmers in Ethiopia. Analog to vegetable, production adoption of Potato and onion also play a great role in improving the daily livelihood of farmers. However, there are few studies on its technology adoption to encourage farmers to substitute their production methods by modern production techniques and maximize return from the sector. The objective of this review paper is to review determinant factors of vegetable technology package adoption in Ethiopia by using the finding of popular published empirical researches. The findings of the review identified that, adoption of potato and onion technologies in Ethiopia is low due to different constraints caused by demographic factors, socio-economic factors, institutional factors and technological factors. Similarly, different empirical researches which are reviewed by this 0review paper identified different types of potato and onion production technology packages like improved seed varieties, fertilizers, quality seed, irrigation services, crop protection methods, and storing house.As a result of the above combinations of vegetable production technology adoption factors, the expected outcome to be obtained from the sector is still poorly performed. By considering the importance of these potato and onion production technology packages, applying and implementing the procedures of adoption bring the decision to adopt technologies and improve the extent of it thereby sustain potato and onion production in Ethiopia.